Synthesis, Characterization of Di-1, 3-Oxazepine and Evaluation of their Antimicrobial Activity against Molecular Diagnostic Bacterial Isolates - Nadia A. Salih (Journal of Global Pharma Technology, 2018)
This work presents Two Schiff bases derived from 4, 4'-Diaminodiphenylmethane, distinguished by the para substituted halogen of benzaldehyde. These Schiff bases used to synthesis of four compounds of di-1, 3-oxazepine by direct condensation with tetrachloro phthalic anhydride and tetrabromophtalic anhydride. All structures were characterized by using spectroscopic techniques such as FT- IR, 1H-NMR, 13C-NMR. The synthesized compounds were screened as an anti-bacterial agent against bacterial strains (Gram positive S. aureus and Gram-negative P. aeruginosa and K. pneumonia) which were diagnosed using high specific method “genetic method for S. aureus and P. aeruginosa and Vitec 2 for K. pneumonia.Keywords: Schiff bases, 1, 3-Oxazepine, Tetrachlorophthalic anhydride, Antibacterial activity.